The taxonomic status of recently described Isophya taxa from Serbia (Tettigoniidae, Phaneropterinae) - Ivković, Slobodan; Dey, Lara-Sophie; Horvat, Laslo; Iorgu, Ionuț Ștefan; Buzzetti, Filippo Maria; Hochkirch, Axel (European Journal of Taxonomy, 2024)
During recent decades, increasing research of the taxonomy of the genus Isophya resulted in taxonomic descriptions of several new species. The delimitation of these species is mainly based on oscillographic song analysis of the male song in combination with morphological characters, such as the shape of male cerci, tegmina and ovipositor. In the present paper, we used an integrative taxonomic approach in order to resolve the status of four recently described Isophya taxa from Serbia. Based on our molecular and bioacoustic analyses, all analyzed taxa belong to a single species: Isophya modestior. The majority of the morphological characters used to differentiate the taxa showed strong intra- and interpopulational variability, proving that describing new species within the genus Isophya should not rely on morphological characters alone, but needs to consider bioacoustic analyses as the main tool and a larger series of specimens.